Lymphocyte Recovery Predicts Outcomes in Cord Blood and T Cell–Depleted Haploidentical Stem Cell Transplantation - Ciurea, Stefan O. (Biol Blood Marrow Transplant, 2010)
Alternative donor stem cell transplantation from cord blood or haploidentical peripheral blood donors is increasingly being used for patients who lack a matched related or unrelated donor. A higher nonrelapse mortality (NRM) rate has been noted with these 2 types of transplants, primarily because of infectious complications. Here, we hypothesized that the time to lymphocyte recovery (absolute lymphocyte count [ALC] of ≥ 1000/μL for the first 3 consecutive days) after transplant correlates with outcomes. We retrospectively analyzed 65 consecutive patients treated at our institution with cord blood (n = 37) and haploidentical (n = 28) transplantation with myeloablative fludarabine, melphalan, and thiotepa conditioning. Patients with lymphocyte recovery at day 60 posttransplant were more likely to survive long term than those without lymphocyte recovery. In multivariate analysis, ALC recovery was the only independent prognostic factor associated with mortality; patients without ALC recovery were 10.5 times (95% confidence interval [CI]: 4.3–25.4) more likely to die than those with ALC recovery (P < .0001). This difference appeared to be related to NRM (hazard ratio [HR] =0.1, 95% CI: 0.02–0.6, P = .008), whereas ALC recovery did not influence the rate of disease relapse. These results suggest that ALC recovery is an important prognostic indicator for patients treated with cord blood and T cell–depleted peripheral haploidentical transplants.